The use of the multifunctional resources rooms for science teaching: a study on inclusion (Research, Society and Development, 2019)
The present article intends to present a clipping of the results obtained in a research of Monography that aimed to analyze and describe how the public schools of a county located in the state of Minas Gerais, Brazil, employ the Multifunctional Resource Rooms (SRM) in order to teach Science and Biology to the students of the Special Education Section (PAEE), since Education is every person’s right, whether they have some disability or not. It is known that the current educational policy of Special Education presentes. Inclusive features: the legislation recommends the Specialized Educational Assistance (ESA) of students with disabilities, global developmental disorders and high abilities / giftedness, to happen preferably in the regular school, in the called Multifunctional Resource Rooms. In this way, one of the AEE assignments is to assure articulation between the teachers of the common class, in order to establish, in partnership with them, strategies that guarantee the learning of the PAEE students. Through an exploratory qualitative approach, a field study was made, using semi-structured interviews as a method of data collecting from teachers who work in the SRM of middle and high schools. The data were analyzed according to qualitative criteria, and then clustered in similar signification cores. It was possible to conclude that, despite the legal efforts at the Federal level to ensure the education of the PAEE students, attitude changes are still necessary for teachers and school management to ensure quality, heterogeneity and inclusive science teaching.